1985
DOI: 10.1080/03014468500008031
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and mortality differences in relation to maternal body size

Abstract: The relationship between maternal stature, number of conceptions, offspring mortality and number of surviving children was studied in 291 Jalari women. Maternal stature averaged 150.98 cm, maternal age 35 years, number of conceptions 5.1 and number of surviving children 4.2. Adjusting for age and number of conceptions, the relationship between maternal stature and surviving children is significantly negative. Shorter women show significantly higher number of conceptions and surviving children than taller women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 2 publications
3
10
1
Order By: Relevance
“…Some prior studies (Devi et al, 1985;Frisancho et al, 1973;Kirchengast, 2000;Lasker and Thomas, 1976;Strickland and Tuffrey, 1997) appear not to be in line with our main finding, because they report no association or non-linear associations between maternal height and offspring survival. The discrepancy is not that stark, however.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Some prior studies (Devi et al, 1985;Frisancho et al, 1973;Kirchengast, 2000;Lasker and Thomas, 1976;Strickland and Tuffrey, 1997) appear not to be in line with our main finding, because they report no association or non-linear associations between maternal height and offspring survival. The discrepancy is not that stark, however.…”
Section: Discussioncontrasting
confidence: 54%
“…However, not all studies on this relationship in developing countries point in the same direction. Negative effects have been reported for India and Peru (Devi et al, 1985;Frisancho et al, 1973), no effects for Namibia and Brazil (Kirchengast, 2000;Menezes et al, 2005) and nonlinear effects for Nepal and Papua New Guinea (Brush et al, 1983;Strickland and Tuffrey, 1997). Although these findings are based on specific and non-representative populations, they indicate that also within developing countries the effect of maternal height could depend on ecological factors, including the situation of the household.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Further research has demonstrated that women have stronger preferences for tall men during the fertile phase of their menstrual cycle (Pawlowski & Jasienska, 2005), and that women's height preferences in men are positively predicted by conformity to views on traditional gender roles and positively correlate with personality traits such as self-esteem and extraversion (Swami et al, 2008). Consistent with reported height preferences, there is some evidence that taller men (Mueller & Mazur, 2001;Pawlowski, Dunbar, & Lipowicz, 2000), and short (Devi, Kumari, & Srikumari, 1985) or average height women (Mueller, 1979;Nettle, 2002;Vetta, 1975) have greater reproductive success than people of other heights, though these effects are not replicated in all studies. See Sear (2010) and Stulp, Pollet, Verhulst, and Buunk (2012) for a full review of studies on height and reproductive success.…”
Section: Introductionsupporting
confidence: 66%
“…By contrast, one study of a sample of lower caste Indian women found negative effects of height on reproductive success, with taller women having lower fertility and lower numbers of surviving children (Devi et al, 1985). Some studies have also failed to find any relation at all between maternal height and reproductive success (Bailey and Garn, 1979;Kirchengast, 2000;Lasker and Thomas, 1976).…”
mentioning
confidence: 90%